2013
DOI: 10.1097/rlu.0b013e3182708777
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hypoxia With 18F-Fluoromisonidazole (18F-FMISO) PET/CT in Suspected or Proven Pancreatic Cancer

Abstract: The hypoxia imaging agent, FMISO, demonstrates minimal activity in pancreatic tumors. If FMISO PET/CT is to be included in clinical trial protocols of hypoxia in pancreatic cancer, it would require correlation with other imaging modalities to localize the tumor and allow semiquantitative analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 22 publications
0
30
1
Order By: Relevance
“…In contrast, our results showed more clustered areas of hypoxia, with good repeatability. Compared to an earlier in vivo study where [ 18 F]FMISO hypoxia imaging was performed in pancreatic cancer, we observed higher image contrast and were better able to visually identify areas with increased tracer uptake [48]. This could well be explained by the longer time between injection and scanning (2 h vs. 3.5 h) and the faster background clearance of [ 18 F]HX4 compared to [ 18 F]FMISO [38].…”
Section: Discussioncontrasting
confidence: 40%
“…In contrast, our results showed more clustered areas of hypoxia, with good repeatability. Compared to an earlier in vivo study where [ 18 F]FMISO hypoxia imaging was performed in pancreatic cancer, we observed higher image contrast and were better able to visually identify areas with increased tracer uptake [48]. This could well be explained by the longer time between injection and scanning (2 h vs. 3.5 h) and the faster background clearance of [ 18 F]HX4 compared to [ 18 F]FMISO [38].…”
Section: Discussioncontrasting
confidence: 40%
“…Koh et al [221] , Liu et al [222] , Yeh et al [223] , Rischin et al [224] , Bentzen et al [125] , Rajendran et al [225] , Gagel et al [126] , Rajendran et al [226] , Hicks et al [227] , Lawrentschuk et al [200] , Loi et al [228] , Thorwarth et al [229] , Rajendran et al [230] , Rischin et al [231] , Thorwarth et al [232] , Zimny et al [124] , Eschmann et al [233] , Gagel et al [202] , Thorwarth et al [234] , Thorwarth et al [235] , Lee et al [236] , Lin et al [237] , Nehmeh et al [238] , Roels et al [239] , Dirix et al [240] , Lee et al [241] , Mortensen et al [127] , Wang et al [56] , Abolmaali et al [242] , Bowen et al [138] , Eary et al [243] , Kikuchi et al [244] , Hugonnet et al [131] , Yamane et al [245] , Mammar et al [246] , Zips et al [247] , Cheng et al [217] , Henriques de Figueiredo et al [248] , Okamoto et al [249] , Sato et al [218] , Segard et al [250] , Tachibana et al [251] , Norikane et al [219] [ Dubois et al …”
Section: F]fmisomentioning
confidence: 99%
“…4,5). Two prominent characteristics of pancreatic cancer, hypoperfusion and desmoplasia, play important roles in forming the hypoxic microenvironment (6).…”
Section: Introductionmentioning
confidence: 99%